2006
DOI: 10.1016/j.icesjms.2006.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Size of wild and hatchery-reared Atlantic salmon populations in the northern Baltic Sea estimated by a stratified mark-recapture method

Abstract: J. 2006. Size of wild and hatchery-reared Atlantic salmon populations in the northern Baltic Sea estimated by a stratified mark-recapture method. e ICES Journal of Marine Science, 63: 1477e1487.We estimated the total size of the Atlantic salmon (Salmo salar) population complex (wild and cultured) in the Gulf of Bothnia, northern Baltic Sea, using a stratified mark-recapture method. In 2001In , 1970 salmon were captured by the commercial trapnet fishery and tagged with external arrow tags. A total of 349 tagge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Survival estimates for wild fish tend to be higher than those for hatchery juveniles [19], [57], [68], [75], [76], [81], [92][95]. In one study, survival of wild steelhead smolts during migration away from inshore waters ranged from 18–39%, while hatchery smolt survival was 3% [76].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Survival estimates for wild fish tend to be higher than those for hatchery juveniles [19], [57], [68], [75], [76], [81], [92][95]. In one study, survival of wild steelhead smolts during migration away from inshore waters ranged from 18–39%, while hatchery smolt survival was 3% [76].…”
Section: Resultsmentioning
confidence: 99%
“…pink, masu) are underrepresented in the literature. Most of the research we analyzed examined hatchery fish rather than wild fish, and relatively few tagging studies compared the two (except see [19] , [49] , [50] , [57] , [68] , [75] , [76] , [81] , [92] [95] , [164] , [165] ), despite known differences in behaviour and survival. For example, wild populations commonly display adaptive plasticity in migration timing due to environmental variation and as a means of avoiding interspecies competition [81] , while hatchery raised fish are manually released according to a hatchery schedule [92] .…”
Section: Resultsmentioning
confidence: 99%
“…In many situations power industry is forced to compensate the loss of wild salmon via hatchery-reared salmon stockings. However, it has been observed that reared salmon might be less viable than wild (Siira et al 2006), and there are some indications that wild and reared salmon do not necessarily display similar migratory behaviour (Salminen et al 1994, Kallio-Nyberg et al 2006.…”
Section: Present Threats To Salmonmentioning
confidence: 99%
“…To this end, it is generally believed that hatchery-reared fish are more prone to predation than wild fish due to lower levels of anti-predator behavior in the hatchery-reared fish (Einum & Fleming, 2001;Pedersen et al, 2008;Serrano et al, 2009). However, despite that a strong effect of origin (hatchery compared with wild) on juvenile to adult survival has been found in Baltic sea salmon (Kallio-Nyberg et al, 2006;Saloniemi et al, 2004;Siira et al, 2006), a difference in mortality and predation risk between hatchery-reared and wild fish during the juvenile life stages has generally not been documented for Atlantic salmon (Fl avio et al, 2021;Gudjonsson et al, 2005;Hvidsten & Lund, 1988;Hyvärinen et al, 2006;Kennedy & Greek, 1988;Lacroix, 2008;Thorstad et al, 2007). For sea trout, on the other hand, a difference in juvenile survival between hatchery-reared and wild fish has been found, with wild juveniles often having a higher survival and lower predation mortality than hatchery-reared juveniles (Aarestrup et al, 2014;Dieperink et al, 2001;Serrano et al, 2009).…”
Section: Introductionmentioning
confidence: 99%